A Landscape Archive: Methods for Interaction Design, Preservation, Access, and Mapping—A Case Study. Issue 3 (2nd October 2017) - Joy, Cillian; Keane, Aisling; Corrigan, Peter
ABSTRACT: The National University of Ireland, Galway (NUI Galway) acquired the archive of Tim Robinson in 2013. Robinson is a cartographer and writer who lived, studied, and documented the landscape surrounding Galway Bay over the course of 40 years. This article describes the methods taken for the digital preservation, access provision, discovery, and digital mapping of this landscape archive. It describes a user interface that allows exploration and discovery of the landscape archive on a digital map, linked to the archive, which allows the user to interact with the material from a perspective of place. The aim of this is to provide an enhanced user experience and create potential for teaching, research, and community engagement. The archive can also be accessed using more traditional hierarchical archival discovery interfaces and is selectively digitally preserved and accessible as a digital archive.